2005
DOI: 10.1002/bltj.20095
|View full text |Cite
|
Sign up to set email alerts
|

Novel algorithms for efficient exploration of the tradeoffs between cell count and performance in wireless networks

Abstract: performance with fewer cells, integrating these performance gains with existing infrastructure creates additional design challenges. Lucent and its competitors therefore must be able to design and optimize next-generation wireless networks with the additional constraints of an existing base of assets.No single design objective will meet the needs of every service provider in every market; instead, design objectives must be considered on a market-by-market basis. Decisions that balance equipment and operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The channel capacity C for a channel perturbed by additive white Gaussian noise is a function of the average received signal power P Rx ϭ E{s(t)s(t)*}, the average noise power P N ϭ E{n(t)n(t)*}, and the bandwidth B, where s(t) and n(t) denote the signal and noise values at the time instant t. The well-known capacity relationship (Shannon-Hartley theorem [18]) can be expressed as (1) In order to write equation 1 in terms of transmitted power P Tx , the impact of the channel loss L ϭ L p L s , characterized as a combination of attenuations resulting from path loss L p and shadow fading L s , must be taken into account. Note that this requires knowledge of the positions of the connected mobile devices and knowledge of the environment (i.e., shadow fading properties).…”
Section: Power Requirement For a Link With Given Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The channel capacity C for a channel perturbed by additive white Gaussian noise is a function of the average received signal power P Rx ϭ E{s(t)s(t)*}, the average noise power P N ϭ E{n(t)n(t)*}, and the bandwidth B, where s(t) and n(t) denote the signal and noise values at the time instant t. The well-known capacity relationship (Shannon-Hartley theorem [18]) can be expressed as (1) In order to write equation 1 in terms of transmitted power P Tx , the impact of the channel loss L ϭ L p L s , characterized as a combination of attenuations resulting from path loss L p and shadow fading L s , must be taken into account. Note that this requires knowledge of the positions of the connected mobile devices and knowledge of the environment (i.e., shadow fading properties).…”
Section: Power Requirement For a Link With Given Capacitymentioning
confidence: 99%
“…Other work has explored the trade-offs among coverage, cell count, and capacity [1]. It has been shown that the identification of globally optimum base station positions in a network is an NP-hard problem far too complex to solve computationally [12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Our work uses similar techniques, albeit in a different context. In [7] and [8], a heuristic algorithm was developed to determine the cell sites selection problem during upgrading from 2G to 3G. The objective was to determine a solution which minimised cell count and associated costs while continuing to satisfy the user demand during the upgrade.…”
Section: IImentioning
confidence: 99%
“…Constraint (7) ensures every TP is assigned to either a BS or an RS. Constraint (8) ensures every RS assigned to only one BS; also if the RS is not installed, it cannot be assigned to a BS. Constraints (9), (10) and (11) ensure that TPs are not assigned to BSs that are not present, TPs are not assigned to RSs that are not present and RSs are not assigned to BSs that are not present respectively.…”
Section: A Problem Formulationmentioning
confidence: 99%
“…Other work has explored the trade-offs between coverage, cell count and capacity [8]. It has been shown that the identification of the globally optimum base station locations in a network of multiple base stations is an NP-hard problem, far too complex to solve computationally [4][5][6].…”
Section: Introductionmentioning
confidence: 99%